2022
DOI: 10.3389/fvets.2021.793427
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age and Dietary Factors on the Blood Beta-Hydroxybutyric Acid, Metabolites, Immunoglobulins, and Hormones of Goats

Abstract: The study was aimed to examine the effects of age and dietary beta-hydroxybutyric acid (BHBA) on blood BHBA and blood health indicators in goat kids. Thirty male goats of five ages (1, 2, 3, 6, and 12 months old) were selected for blood sampling to determine the influence of age. Another 64 goat kids (half males and half females) were weaned at 1 month old and fed with starter diets with control, low, medium, and high BHBA doses (0, 3, 6, and 9 g/animal/day, respectively). Six goats per treatment were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Previous studies in humans and mice found that ketone bodies increased the blood and luminal BHB (Olson et al, 2018 ; Ang et al, 2020 ). This might be due to the specific anatomy of rumen epithelium that utilized more BHB or VFAs for its rapid development of the ketogenic capacity in young ruminants (Lane et al, 2002 ; Abdelsattar et al, 2022b ; Wang et al, 2022 ). In the meantime, a low dose of BHB feeding increased rumen VFAs, including acetate, propionate, and butyrate, while medium and high doses affected them.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in humans and mice found that ketone bodies increased the blood and luminal BHB (Olson et al, 2018 ; Ang et al, 2020 ). This might be due to the specific anatomy of rumen epithelium that utilized more BHB or VFAs for its rapid development of the ketogenic capacity in young ruminants (Lane et al, 2002 ; Abdelsattar et al, 2022b ; Wang et al, 2022 ). In the meantime, a low dose of BHB feeding increased rumen VFAs, including acetate, propionate, and butyrate, while medium and high doses affected them.…”
Section: Discussionmentioning
confidence: 99%